Sistem Deteksi Dan Pemantauan Kualitas Udara Dalam Ruangan Berbasis IoT - Aqila Zulfahmi Putri, Nessa; Uray Ristian; Rahmi Hidayati (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The indoor air quality is related to the comfort and health of the people inside. The causes of poor air quality or stuffiness can be influenced by three parameters: temperature, humidity, and the levels of carbon dioxide. To detect air quality, an IoT-based system was developed to monitor the status of indoor air quality. The air quality statuses defined in this study include not stuffy, moderately stuffy, stuffy, or very stuffy. The sensors used in this study are DHT11 and MH-Z19B. Testing was conducted in three different rooms: Computer Laboratory A, Computer Laboratory B, and the Workshop Laboratory of the Computer System Engineering program at Tanjungpura University, Pontianak. The results of this study include a device that displays information on temperature, humidity, and carbon dioxide levels on a 16x2 LCD with LED lights that turn on when parameter values exceed the set thresholds, and a website. The average detected temperature was 27.51Â°C, humidity was 52.34%, and the average carbon dioxide level was 703.36 PPM. Based on these three parameters, the average detected air quality status was moderately stuffy. The system was able to detect indoor air quality with an overall average system accuracy of 90.31%.